Pengendalian Kualitas Produksi Krupuk Rambak Pada UD. Special (Program Studi Ilmu Administrasi Bisnis, 2022)
The purpose of this study is to identify and describe the process of controlling the quality of cracker rambak products carried out by UD. Special in dealing with products that are not up to standard. The research method used is descriptive qualitative. The result of this research is that business owners are directly involved in quality control. Quality control is carried out together with production employees. Control is carried out in the input, transformation and output stages. Product defects occur in the input stage where employees sometimes make mistakes in producing the product, causing the product to not meet the standards.